Dynamics of Executive Functions, Basic Psychological Needs, Impulsivity, and Depressive Symptoms in American Football Players - Rincón Campos, Yahel Enith; Sanchéz López, Javier; López Walle, Jeanette M.; Ortiz Jiménez, Xóchitl A. (Frontiers Research Foundation, 2019)
Executive functions play an important role in sports since the ability to plan, organize,and regulate behavior to reach an objective or goal depends on these functions. Someof the components of executive functions, such as inhibition of impulsive behavior andcognitive flexibility, are necessary for contact sports (e.g., American football) to carryout successful plays on the sports field. Executive functions have been studied in thesporting environment, but their relationship with the athletes’ basic psychological needs(BPN), such as autonomy, competence, and relatedness, remains unexplored. Due tothe importance of motivational processes over cognitive functions and in the generatedadaptive results in athletes, this relationship should be taken into account. Therefore, theaim of this study was to analyze and compare executive functioning and psychologicalneed thwarting overimpulsivity and psychological distress, before and after the season(4 months) in 28 undergraduate football players. Neuropsychological and psychologicaltests were applied. The results showed that there was an improvement in inhibitionand planning at the end of the season. There was also an increase in attention andmotor impulsiveness, and a decrease in need thwarting at the end of the season.A positive association between executive function, impulsiveness, psychological needs,and affective symptoms were also found. Our findings reveal the dynamics of sport-related psychological variables throughout the sport season in American football players,the association of these for the achievement of sport success, and the importance ofencouraging proper management of emotions.